Self-Cutting and Suicide Risk Among Adolescents: The Case of the “Blue-Whales” - Francesco Lupariello; Serena Maria Curti; Elena Coppo; Sara Simona Racalbuto; Ignazio Grattagliano; Giancarlo Di Vella (American Academy of Forensic Sciences, 2018)
After attending this presentation, attendees will understand the importance of training healthcare staff to promptly recognize suicidal risk behaviors among adolescents. This presentation will impact the forensic science community by providing information regarding the media phenomenon known as the “Blue-Whale-Challenge,” which includes self-cutting; this carries a high potential risk of suicide. The Blue-Whale-Challenge is a dangerous internet phenomenon that consists of a series of duties, imposed by an administrator to players who must complete a list of actions involving self-mutilation. The game lasts 50 days, with players usually completing one duty per day, and ends with the suicide of the player.1 The term “Blue-Whale” results from the similarity of suicidal behavior among beached whales. The phenomenon began in 2013, in Russia, on the “VKontakte” social network, with the first case of suicide in 2015. The inventor was a psychology student, expelled from his university. The student said that his purpose was to clean society of people of no value.2 The phenomenon spread among teenagers in Russia, then in other areas, due to the media resonance caused by television broadcasts and newspaper articles that featured information regarding the game. After a wave of panic caused by an article concerning the many suicides related to the Blue-Whale phenomenon in Russia, the inventor was arrested in 2016. Around the world, the phenomenon accounts for many cases, some of which have often turned out to be hoaxes or emulators. In Italy, the first news about the Blue-Whale appeared in June 2016 in a national newspaper, but only in May 2017 did a well-known television program deal with the subject, using reports that did not quote official sources. From that moment on, the police began receiving calls and newspapers published alarming news concerning Blue-Whale incidents, which were often quickly denied. Between May and June 2017, five suspected cases of Blue-Whale have been managed by the officers of the unit. The ...